Primary care drug therapy pharmacists in South Africa: Practice settings and conditions treated - Maxine Tromp; Ilse Truter; Jan du Toit (Elsevier, 2023)
Background: Primary Care Drug Therapy (PCDT) is a supplementary training course for South African pharmacists. The qualification affords pharmacists an expanded scope of practice to treat specific primary health care conditions. Objective: To describe the practice settings and conditions being treated by PCDT pharmacists in South Africa, with specific focus on differences between services delivered in urban versus rural areas. Methods: An online questionnaire survey was conducted under all PCDT trained pharmacists in 2021. Results: Less than half (45.3%; n = 34) of the 75 respondents had received their Section 22 A(15) permit and were practicing as PCDT pharmacists. Of these respondents, only 41.2% were practicing in a rural setting. Overall, respondents indicated that ear, nose and throat conditions, and family planning, were the most often consulted conditions. Differences were, however, observed between provinces, and between urban and rural areas. Family planning, urological conditions and sexually transmitted infections were most frequently consulted in urban areas, whilst gastrointestinal conditions, and ear, nose and throat conditions, were more common in rural areas. Conclusions: Conditions treated in the different settings in South Africa provided a unique insight into the epidemiological profile of the area, as well as the primary health care needs.